Effect of Leverage, Previous Year's Audit Opinion and Company Growth on Going Concern Audit Opinion - Shufia Zuhroh; Yudhi Prasetiyo; Novita Nugraheni; Etik Ipda Riyani (International Journal of Business and Applied Economics, 2023)
The purpose of this study is to determine the effect of leverage, the previous year's audit opinion, and company growth ongoing concern audit opinions, in various industrial companies listed on the Indonesia Stock Exchange for the 2016-2021 period. The method of data analysis in this study is multiple linear regression analysis which is pooled data where the software used is Eviews.9. The results showed that leverage had a negative and insignificant effect on going-concern audit opinions, while the previous year's audit opinion and company growth had a positive and significant effect on going-concern audit opinions.